Pengembangan Pariwisata Berkelanjutan di Pantai Padang: Ditinjau dari Efektivitas Pengembangan Fasilitas dan Infrastruktur - Wahyuni, Nila (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This research is motivated by sustainable tourism and its relevance to the development of facilities and infrastructure on Padang Beach. Preliminary data shows an increase in the number of tourist visits to Padang Beach, indicating continued increasing interest in this destination. This article aims to analyze the effectiveness of the facilities and infrastructure development program at Padang Beach in achieving sustainable tourism goals. This research uses a descriptive qualitative approach involving 14 informants in May 2023. The research results reveal that several challenges still need to be overcome in developing sustainable tourism on Padang Beach. Improving service quality is still not optimal; there needs to be more local community involvement, as well as infrastructure challenges such as inadequate public transportation, inadequate parking, and a lack of public facilities such as toilets. Environmental management must also be improved to reduce negative impacts on coastal and aquatic ecosystems. Based on the results and discussion, this article concludes that further efforts must be made to enhance the quality of service, involve local communities in tourism development, overcome infrastructure challenges, and improve the environmental management at Padang Beach. This research is hoped better to understand the effectiveness of facilities and infrastructure development programs and provide input for policies and practices for sustainable tourism development in other destinations.